Nondestructive discrimination of Bell states between distant parties - Bilash, Bohdan; Lim, Youngrong; Kwon, Hyukjoon; Kim, Yosep; Lim, Hyang-Tag; Song, Wooyeong; Kim, Yong-Su (American Physical Society, 2024)
Identifying Bell states without destroying them is frequently dealt with in quantum technologies nowadays, such as in quantum communication and quantum computing. In practice, quantum entangled states are often distributed among distant parties, and it might be required to determine them separately at each location, without inline communication between parties. We present a scheme for discriminating an arbitrary Bell state distributed to two distant parties without destroying them. The scheme requires two entangled states that are preshared between the parties and we show that, without these ancillary resources, the probability of nondestructively discriminating the Bell state is bounded by 1/4, which is the same as random guessing. Furthermore, we demonstrate a proof-of-principle experiment through an IonQ quantum computer that our scheme can surpass classical bounds when applied to a practical quantum processor.